Clavis to the metrical homilies of Narsai - Butts, Aaron Michael (Corpus scriptorum Christianorum orientalium, 2021)
Narsai (died approximately 500) is a foundational East Syriac theologian and exegete and among the most important and influential Syriac authors more broadly. The present volume serves as a clavis to the more than eighty metrical homilies (memre) attributed to him. The first part consists of the clavis itself: It is organized by homily providing for each a number, a short title, the incipit, the manuscript attestation, previous editions and translations, previous scholarship, and additional notes, when applicable. The second part is a study of manuscripts that contain collections of homilies attributed (primarily) to Narsai. For each manuscript, the following information is provided: date, catalogue-type description of contents, bibliography, and notes. The third part is a series of concordances that link the present work to previous publications as well as to the incipits. The volume also contains a curated bibliography on Narsai